Analysis of Communication Patterns and Social Networks in Digital Journalism on the Palestine-Israel Conflict - Weninggalih, Prawiro; Pramiyanti, Alila (Dinasti Research, 2025)
This study aim to analyze the patterns of communication and social networks accompanying digital journalism in relation to the conflict of Palestine-Israel. Using SNA and the analysis of narrative patterns, this research tries to find how social media has become the big site for public opinion production of the considered conflict. The findings highlight a polarized social media communication between the pro-Palestinian and pro-Israeli groups, while neutral actors serve as a kind of bridge trying to maintain the balance of information. In addition, in the narrative pattern analysis, five main topics dominate the conversation: physical conflict and its impact; religious responses and global solidarity; international context and human rights; media coverage and location focus; politics and regional dimensions. It also shows that while social media is a great avenue to get information out quickly, there are considerable drawbacks in terms of the biases and misinformation that may be taken as factual input in influencing international policies in strengthening social movements. This paper highlights the need to be aware of the power of narrative patterns in digital communication and the need for more critical and ethical use of social media as a tool for communication.